The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fgene.2022.982418
|View full text |Cite
|
Sign up to set email alerts
|

A consensus map for quality traits in durum wheat based on genome-wide association studies and detection of ortho-meta QTL across cereal species

Abstract: The present work focused on the identification of durum wheat QTL hotspots from a collection of genome-wide association studies, for quality traits, such as grain protein content and composition, yellow color, fiber, grain microelement content (iron, magnesium, potassium, selenium, sulfur, calcium, cadmium), kernel vitreousness, semolina, and dough quality test. For the first time a total of 10 GWAS studies, comprising 395 marker-trait associations (MTA) on 57 quality traits, with more than 1,500 genotypes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Markers from the selected QTL hotspots were launched against the mapping pipeline of the Brachypodium, rice and maize genomes, as reported in Marcotuli et al [ 26 ]. Twenty-four out of the 33 selected QTL hotspots reported collinearity with the other genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers from the selected QTL hotspots were launched against the mapping pipeline of the Brachypodium, rice and maize genomes, as reported in Marcotuli et al [ 26 ]. Twenty-four out of the 33 selected QTL hotspots reported collinearity with the other genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Search for syntenic regions in Brachypodium distachyon , Oryza sativa and Zea mays was performed as reported in Marcotuli et al [ 26 ]. The following reference genomes were used: Brachypodium distachyon version 1 ( , accessed on 1 September 2022); Oryza sativa Japonica Group version IRGSP-1.0 ( , accessed on 1 September 2022), Zea mays version AGPv3 ( , accessed on 1 September 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Important data on the genetic dissection of gluten-related traits were obtained for durum wheat, including elite cultivars, landraces, breeding lines, and subspecies. Orthometa QTL analysis across cereal species, conducted on the basis of ten GWAS studies for varieties and species of durum wheats, revealed hot spot QTLs for grain protein content and gluten index in chromosomes 1A, 1B, 3B, 5A, 6A, and 7A [67]. In another study, Jonson et al [25] analyzed 24 traits related to protein content, gluten strength, cooking, and milling quality, wherein major and stable QTLs for gluten-related traits were identified on chromosomes 1A and 1B.…”
Section: Comparison Of Putative Qtl Localization With Known Datamentioning
confidence: 99%
“…Meta-QTL analysis has been successfully performed in bread wheat for yield and related traits ( Zhang et al., 2010 ; Liu et al., 2020 ; Miao et al., 2022 ; Saini et al., 2022a ), grain quality traits ( Tyagi et al., 2015 ), mineral content ( Singh et al., 2022 ), fusarium head blight (FHB) resistance ( Löffler et al., 2009 ; Venske et al., 2019 ; Saini et al., 2022b ), and abiotic resistance ( Xu et al., 2017 ; Guo et al., 2023 ). In durum wheat, MQTL has been conducted for yield and related traits ( Arriagada et al., 2022 ); quality traits, abiotic and biotic stressors ( Soriano et al., 2021 ); pasta making quality ( Roselló et al., 2018 ); GPC ( Saini et al., 2022c ); and ortho-MQTL analysis for quality traits ( Marcotuli et al., 2022 ). To the best of our knowledge, the only MTQL study performed using wild emmer was carried out by Avni et al.…”
Section: Introductionmentioning
confidence: 99%